Low- and high-frequency oscillations reveal distinct absence seizure networks - Tenney, Jeffrey R.; Fujiwara, Hisako; Horn, Paul S.; Vannest, Jennifer; Xiang, Jing; Glauser, Tracy A.; Rose, Douglas F. (Annals of neurology, 2014)
Objective The aim of this study was to determine the frequency‐dependent, spatiotemporal involvement of corticothalamic networks to the generation of absence seizures. Methods Magnetoencephalography recordings were obtained in 12 subjects (44 seizures) with untreated childhood absence seizures. Time‐frequency analysis of each seizure was performed to determine bandwidths with significant power at ictal onset. Source localization was then completed to determine brain regions contributing to generalized spike and wave discharges seen on electroencephalogram. Results Significant power in the time‐frequency analysis was seen within 1 to 20Hz, 20 to 70Hz, and 70 to 150Hz bandwidths. Source localization revealed that sources localized to the frontal cortex similarly for the low‐ and gamma‐frequency bandwidths, whereas at the low‐frequency bandwidth (3–20Hz) significantly more sources localized to the parietal cortex (odds ratio [OR] = 16.7). Cortical sources within the high‐frequency oscillation (HFO) bandwidth (70–150Hz) localized primarily to the frontal region compared to the parietal (OR = 7.32) or temporal (OR = 2.78) areas. Interpretation Neuromagnetic activity within frontal and parietal cortical regions provides further confirmation of hemodynamic changes reported using functional magnetic resonance imaging that have been associated with absence seizures. The frequency‐dependent nature of these networks has not previously been reported, and the presence of HFOs during absence seizures is a novel finding. Co‐occurring frontal and parietal corticothalamic networks may interact to produce a pathological state that contributes to the generation of spike and wave discharges. The clinical and pathophysiological implications of HFOs within the frontal cortical region are unclear and should be further investigated. Ann Neurol 2014;76:558–567